2012
DOI: 10.3892/ijo.2012.1398
|View full text |Cite
|
Sign up to set email alerts
|

Alternariol induces DNA polymerase β expression through the PKA-CREB signaling pathway

Abstract: Abstract. Alternariol (AOH) is a mycotoxin of Alternaria alternata and can cause DNA damage and gene mutations. Low-dose and long-term treatment with AOH has been linked with incidence of esophageal carcinoma. DNA polymerase β (polβ) is a key enzyme in DNA base excision repair (BER). When it is overexpressed or mutated in cells, DNA polβ can cause genetic instability. Elevated DNA polβ has also been reported in several human cancers. Here, we report that AOH at 2, 10, 20 µM induces DNA polβ expression. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…ORMDL3 activates ATF6, increasing the transcription of cAMP response element responsive genes; thus, ORMDL3 may mediate its own expression via a positive feedback loop. In addition, Alternariol, a mycotoxin of Alternaria , increases cAMP response element binding protein binding to CREs 39 and this may be the mechanism by which Alternaria increases ORMDL3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…ORMDL3 activates ATF6, increasing the transcription of cAMP response element responsive genes; thus, ORMDL3 may mediate its own expression via a positive feedback loop. In addition, Alternariol, a mycotoxin of Alternaria , increases cAMP response element binding protein binding to CREs 39 and this may be the mechanism by which Alternaria increases ORMDL3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although this process has been known for decades, the regulation of PKA translocation is not fully understood. Some previous works indicated that failure of PKA catalytic subunit translocation largely impairs CREB phosphorylation [ 46 ]. Our results are consistent with the fact that translocation of the PKA-Cα subunit into the nucleus is required for CREB phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that the POLB gene contains a CRE site in its core promoter essential for full promoter activity (Englander & Wilson, 1990;Widen et al, 1988;Yamaguchi et al, 1994). Moreover, previous studies have shown that POLB expression is stimulated in a CREB-dependent manner in response to DNA damaging agents in mammalian cell lines (He et al, 2003;Kedar et al, 1991;Narayan et al, 1995Narayan et al, , 1996Wang et al, 2001;Zhao et al, 2012). However, in primary cortical neurons many previously investigated stimuli, which alter APE1 in a CREB-mediated way, do not appear to affect POLB expression notably.…”
Section: Discussionmentioning
confidence: 99%